Depression and suicide: the adolescent facing sociocultural risk factors (Research, Society and Development, 2019)
This study aims to emphasize the social aspects related not only to the figure of the adolescent and his adolescent process, but also to the pathology of depression and the relationship with suicidal behavior. In order to reach a broad panorama, an integrative review bibliographic research was carried out and the approach adopted was the qualitative one. As a result, it was found that the social issues surrounding the adolescent are capable of both triggering depression and suicidal behavior in adolescents and influencing the intervention of health professionals with these young people. Thus, it was concluded that there is a great need to break with socially constructed stigmas in order to have qualified care in relation to these adolescents.